The Influence of Perception, Motivation, Attitude, and Lifestyle on Purchasing Decisions at Salapan Coffee - Enok Nuriah; Herni Justiana Astuti (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of perception, motivation, attitude, and lifestyle on purchasing decisions in Salapan Coffee. The method applied was a quantitative approach with a questionnaire of 130 selected respondents based on purposive sampling criteria where consumers who had visited and had bought food or beverage products at Salapan Coffee. Data measurement using a Likert scale of 1 to 5. The stages of data analysis include validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, F-test, and t-test using SPSS 27. The results of the analysis staded that perception, motivation, attitude, and lifestyle have a positive and significant influence on purchasing decisions. The attitude variable was the dominant factor, with the research model explaining 83.4% of the variation in purchasing decisions, while the remaining 16.6% is was caused by other factors not included in the the research model. The conclusion of the study explains that an increase in purchasing decisions can be achieved by strengthening positive consumer attitudes through improvements in product quality, service, and marketing strategies that are aligned with the lifestyle of the target market in order to maintain competitiveness.